17 Fat water imaging for sub-epicardial gadolinium: enhancing the diagnosis of myocarditis. (March 2019) - Kotecha, Tushar; Martinez-Naharro, Ana; Chacko, Liza; Brown, James; Knight, Dan; Anderson, Sarah; Moon, James; Rakhit, Roby; Gillmore, Julian; Hawkins, Philip; Xue, Hui; Kellman, Peter; et al.
Abstract : Background: Conventional bright-blood late gadolinium enhancement (BB LGE) provides excellent contrast between areas of LGE and normal myocardium. Conversely, contrast between LGE and epicardial fat is frequently poor making the detection of sub-epicardial LGE difficult. Sub-epicardial LGE is a sensitive and specific pattern of LGE classically described in myocarditis. However, in practice, patients with a clinical presentation consistent with myocarditis often have no evidence of LGE. Fat water phase sensitive inversion recovery (PSIR) LGE (FW PSIR LGE) is a novel sequence that enables delineation of pericardial fat and may have a role in improving detection of sub-epicardial LGE. Objective: To compare the diagnostic utility of the FW PSIR LGE sequence to standard BB LGE in patients with suspected myocarditis. Methods: Thirty-one patients referred for clinical CMR for suspected myocarditis were studied. A full left ventricle short axis stack was performed using both techniques. Two experienced observers analyzed all BB LGE and FW PSIR LGE stacks. A scoring system was devised to quantify the presence and extent of gadolinium enhancement. Results: All patients (mean age 43±20 years) presented with chest pain and raised troponin (median high sensitivity troponin T 706 ng/L, interquartile range 104–1185 ng/L) and a normal coronary angiogram or very low probability of coronary artery disease. A total of 496 LV segments were analysed. Significantly more segments demonstrated sub-epicardial LGE using FW PSIR LGE compared to BB LGE (122/496 (25%) vs 44/496 (9%), p<0.01). Twelve patients (39%) with no BB LGE (classified as no myocarditis) were found to have sub-epicardial LGE on FW PSIR LGE (therefore reclassified as positive for myocarditis). There was good agreement between the two observers using both sequences (BB LGE: global agreement 80%, kappa 0.72; FW PSIR LGE: global agreement 80%, kappa 0.78, both p<0.001). Conclusions: FW PSIR LGE significantly increases sub-epicardial LGE detection in patients with suspected myocarditis compared to standard bright blood LGE and importantly changes the clinical diagnosis in a third of patients.